SCREENING OF METABOLITE COMPOUNDS OF Chromolaena odorata LEAVES - Santi, Tahara Dilla; Candra, Aditya; Zakaria, Radhiah (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Aceh, 2022)
Background: Chromolaena odorata leaves have been used by the people of Aceh Besar as traditional medicine. The chemical compounds from the leaves of this plant act as antioxidants, anti-inflammatory, antibacterial, and wound healers. The aim of the research was to determine the phytochemical content of C. odorata leaves using qualitative methods. Methods: The extraction method used is maceration and testing of bioactive compounds using a color test. The results showed that the yield percentage is 6.05%. Result: The results of the analysis of phytochemical compounds obtained seven phytochemical compounds contained in C. odorata, namely flavonoids, phenolics, alkaloids, terpenoids, saponins, steroids, and tannins. Recommendation: It is recommended to identify chemical compounds using the GC-MS test to obtain specific compounds that play an active anti-inflammatory, antioxidant, and antibacterial role.